Um olhar para a História nos anos iniciais: concepções e práticas de ensino de História de professoras de uma Escola Municipal de Contagem - Elaine Costa Aguiar (2021)
This work aims to understand aspects of history teaching in the first years of Elementary School. Having a case study as a methodological approach its main objective was to investigate the conceptions and practices of history teaching of five teachers in 4th and 5th grade in a school of Contagem municipality. In order to collect data, the fieldwork had the researcher participating in school meetings, participant observation in history classes, conversation with the school team and responses from a questionnaire answered by participant teachers. Field notes and photographs of various materials was collected and organized as a logbook. In January 2021, a bibliographic study and research by sample with 47 teachers from the first years of Elementary School was carried out in order to understand the main characteristics of a didactic material that meets the demands of students and teachers. On one hand it is taken for granted that historical nature knowledge is an important part of human culture when socialized with children from the first years of life can be permeated by stereotypes and prejudice. On the other hand, specialized historical knowledge from scientific research has a key role for the formation and for the emotional, cognitive and intellectual development of individuals as well as their access occurs, especially, in school. Thus, teachers from the first years of Elementary School can begin with students the process of deconstructing visions of an official History focused on the formation of national identity and contribute to the construction of representation of the past that helps in the construction of thinking historically and of social identities. As results of the investigation by sampling, interactive, dialogical and teaching practices focused on the students was observed and remmant of the conceptions of traditional History among the teachers in the case study. The History National Common Core (BNCC) and Contagem Curricular Reference do not seem to contribute to a renewal in the teaching of History. In relation to the didactic resource, teachers demand an interactive material, with contextualized content and that pedagogically matches the needs of students in the first years of Elementary School. In general, it is considered that the results of this research can contribute to discussions about historical knowledge, history teaching practices, History Didactics, professional development and valorization of teaching knowledge.